INCREASE OF EFFICIENCY OF MODIFIERS FOR GRAY CAST-IRON - O. S. Komarov; N. I. Urbanovich; V. I. Volosatikov; T. D. Komarova (Литьë и металлургия, 2012)
It is established that for the purpose of increase of modifying efficiency of the melt from gray cast iron it is possible to use mechanically alloyed aluminum powder with superdispersed particles of aluminum and graphite oxide.